Gender Equality in the Middle of the Covid-19 Pandemic in the Labor Market - Ni Putu Wiwin Setyari; Ida Ayu Nyoman Saskara; Ananda Putri Pratama Suwitanty; Gusti Ayu Putu Sinta Dewi Lestari (Universitas Negeri Malang, 2023)
The COVID-19 pandemic has accelerated the digitization process in service systems and manufacturing industries in most countries, although at varying speeds. This was triggered by social distancing requirements and other COVID-19-related regulations imposed by governments around the world, including Indonesia. Digital technology is widely regarded as a promising means of promoting gender equality in education, the labor market, access to finance, and health care. This study is aimed at examining whether there are significant differences between female and male workers in the labor market and the digital access they have during the COVID-19 pandemic. The research design used is quantitative. The objects in this study are female and male workers in the province of Bali. In general, the results here confirm indications of increasing gender inequality in Bali. Gender issues are often ignored in gender-related research because technology is believed to be gender-neutral. Male workers have higher productivity than female workers in the labor market. The gender approach argues that technology is not neutral, but dependent on culture. Technology reflects the society that creates it. Access to (and effective use of) technology is affected by a spectrum of exclusions that intersect including gender, ethnicity, age, social class, geography, and disability. The power relations that exist in society determine the enjoyment of the benefits of ICTs, therefore they are not gender-neutral.